Embryonic Stem Cell and Osteogenic Differentiation - Reza Samanipour; Hossein Salehi Rozveh (Negah Institute for Scientific Communication, 2016)
Bone tissue engineering has been one of the most promising areas of research, providing a potential clinical application to cure bone defects. Recently, various stem cells, including embryonic stem cells (ESCs), bone marrow-derived mesenchymal stem cells (BM-MSCs), umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs), adipose tissue-derived stem cells (ADSCs), muscle-derived stem cells (MDSCs), and dental pulp stem cells (DPSCs) have received extensive attention in the field of bone tissue engineering due to their distinct biological capability to differentiate into osteogenic lineages. Application of these stem cells to bone tissue engineering requires their in vitro differentiation into bone forming cells, osteoblasts. For this purpose, efficient in vitro differentiation towards osteogenic lineage requires the development of well-defined and proficient protocols. This protocol would reduce the likelihood of spontaneous differentiation into divergent lineages and increase the available cell source for application to bone tissue engineering therapies. This review article critically examines the various experimental strategies used to direct the differentiation of ESC, BMMSC, UCB-MSC, ADSC, MDSC, and DPSC towards osteogenic lineages and their potential applications in tissue engineering, particularly in the regeneration of bone.